2019
DOI: 10.12693/aphyspola.136.460
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mn Doping on the Structural and Optical Properties of ZnO

Abstract: Zn1−xMnxO (x = 0.00, 0.01, and 0.05, respectively) was synthesized by using solid state reaction method. The structural properties were characterized by using X-ray diffraction and scanning electron microscopy. Optical properties were investigated by UV-visible spectroscopy. X-ray diffraction patterns indicate that all samples have hexagonal wurtzite structure without any impurity phases. The diffraction intensity increases and the peak position shifts to a lower 2θ angle with Mn concentration. The lattice par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 48 publications
(52 reference statements)
6
17
0
1
Order By: Relevance
“…In all these cases there were no impurity of secondary peaks observed as the dopant falls below 30% compared this work. The single-phase hexagonal wurtzite structure of ZnO as was observed in the samples conforms to those of Senol et al [19], Sebayang et al [20] and Bilgili [18]. This is an indication that, the procedure and conditions used for this solid state method is unique since at a low temperature of 200 °C and a high doping concentration of above 20% (Mn < 30%), no additional or secondary phase was observed.…”
Section: Solubility Of Mn In Zno Crystallites Synthesized Using Solidsupporting
confidence: 87%
See 2 more Smart Citations
“…In all these cases there were no impurity of secondary peaks observed as the dopant falls below 30% compared this work. The single-phase hexagonal wurtzite structure of ZnO as was observed in the samples conforms to those of Senol et al [19], Sebayang et al [20] and Bilgili [18]. This is an indication that, the procedure and conditions used for this solid state method is unique since at a low temperature of 200 °C and a high doping concentration of above 20% (Mn < 30%), no additional or secondary phase was observed.…”
Section: Solubility Of Mn In Zno Crystallites Synthesized Using Solidsupporting
confidence: 87%
“…With the work of Sebayang et al (2020), the peak intensity of the Mn doped ZnO nanoparticles was lower than that of the undoped ZnO and also found to be shifted to higher angles at a maximum doping concentration of 9%. Bilgili [18] observed an increase in the intensity of the diffraction peaks and a shift towards lower angles as the doping concentration increases. In all these cases there were no impurity of secondary peaks observed as the dopant falls below 30% compared this work.…”
Section: Solubility Of Mn In Zno Crystallites Synthesized Using Solidmentioning
confidence: 97%
See 1 more Smart Citation
“…The XRD patterns showed that BeO ceramics doped with different Ln 3+ ions synthesized under the same synthesis processes (i.e., calcination and sintering conditions) had the same phase. The XRD patterns do not contain any peaks related to Ln 3+ ions, this may be attributed to the incorporation of Ln 3+ ions into Be 2+ lattice sites rather than interstitial ones [39].…”
Section: Crystal Structurementioning
confidence: 92%
“…Both lattice parameters (a and c) and cell volume (V) were decreased with Ln 3+ doping due to an increase in the existing defect concentration in the lattice. This may be attributed to the larger ionic radius of Ln 3+ compared to that of Be 2+ , hence leading to a lattice contraction [39,40]. Furthermore, The Be-O bond length values obtained from the XRD data of the BeO:Ln 3+ samples are slightly lower than that of the undoped BeO sample (see Table 1.…”
Section: Crystal Structurementioning
confidence: 97%